Persepsi Remaja Putri Cilacap tentang Pernikahan Dini (Sebuah Perspektif Emik dan Etik) - Lailatul Munawaroh; Nurhadi Nurhadi; Yosafat Hermawan Trinugraha (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to answer questions about how young women in Cilacap Regency perceive early marriage and marriage in general. To approach this problem, emic and etic concept references are used. The data were collected in a qualitative way through in-depth interviews with 15 participants. The data obtained were then made in the form of a manuscript to obtain a general description of the object of research. The data from the interviews were analyzed using an emic perspective which was then juxtaposed with objective data using an etic perspective. The criteria for informants in this study were young women aged 15-19 years in Cimanggu District, never married or people who were not involved in marriage, had sufficient time and ability to provide information during the research process, and knew about marriage and early marriage. This study concludes that the negative perceptions of young women in Cimanggu District, Cilacap Regency towards early marriage are (1) the quality of marriage, (2) the things that are sacrificed, (3) health risks, and (4) role responsibilities.